The Struggles and The Survival of Airasia during The Covid-19 Pandemic - Daisy Mui Hung Kee; Yasshni Ramesh Kumar; Vanishree Chadaran; Soniya Karunakaran; Swathy Sugumaran; Tinisma Binti Talha (Advances in Global Economics and Business Journal, 2021)
This study aims to examine AirAsia's struggles during the Covid-19 Pandemic and also examine how AirAsia survive their business during the difficult time. AirAsia is a low-cost Malaysia airline that operates scheduled domestic and international flights. This study used quantitative method and data were collected from 100 Malaysians via online surveys. These circumstances highlight a critical organizational problem that is rarely explored in the literature. The results showed that the main problems occurred were because of the liabilities exceeds assets, border closures and decline in demand, employee job lay off and bankruptcy happened in shares.